(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Tolosa-Hunt Syndrome is an idiopathic granulomatous inflammatory disease of the cavernous sinus, superior orbital fissure, or orbit which is manifested by ocular pain and ophthalmoplegia. Granulomatous inflammation of the dural wall of the cavernous sinus and/or superior orbital fissure is the basis of the pathological process. The disease is clinically manifested by orbital pain, diplopia, exophthalmos, and/or oculomotor abnormalities. The syndrome is also called painful ophthalmoplegia with a key symptom being neuropathic periorbital or retro-orbital pain, and paresthesias along the first branch of the trigeminal nerve. We present a case of this syndrome. The patient was administered hormonal therapy, Medrol at a daily dose of 1 mg/kg body weight/day intravenously for five days, with subsequent transition within a month to oral Medrol. The pain in the eye completely relieved and restoration of normal ocular motility was observed in the presence of hormonal therapy. Tolosa-Hunt syndrome is a clinical diagnosis of exclusion (i.e., it is diagnosed after excluding other causes of painful ophthalmoplegia).